2015
DOI: 10.1139/apnm-2014-0379
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of an arginine-based supplement on neuromuscular, ventilatory, and metabolic fatigue thresholds during cycle ergometry

Abstract: The purpose of the present study was to examine the effects of an acute dose of an arginine-based supplement on the physical working capacity at the fatigue threshold (PWCFT), lactate threshold (LT), ventilatory threshold (VT), and peak oxygen uptake during incremental cycle ergometry. This study used a double-blinded, placebo-controlled, within-subjects crossover design. Nineteen untrained men (mean age ± SD = 22.0 ± 1.7 years) were randomly assigned to ingest either the supplement (3.0 g of arginine, 300 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…17 Participants exercised on a wheelchair ergometer (MOTOmed Reck). 17 Participants exercised on a wheelchair ergometer (MOTOmed Reck).…”
Section: Cardiovascular Endurance and Muscular Endurancementioning
confidence: 99%
See 1 more Smart Citation
“…17 Participants exercised on a wheelchair ergometer (MOTOmed Reck). 17 Participants exercised on a wheelchair ergometer (MOTOmed Reck).…”
Section: Cardiovascular Endurance and Muscular Endurancementioning
confidence: 99%
“…Cardiovascular endurance and muscular endurance of the lower extremities were tested using the physical working capacity of the fatigue threshold test (PWC FT ). 17 Participants exercised on a wheelchair ergometer (MOTOmed Reck). They started with minimum pedal resistance.…”
Section: Cardiovascular Endurance and Muscular Endurancementioning
confidence: 99%
“…The authors (47) reported that compared to the placebo, the pre-workout supplement led to increased time to exhaustion (+12.5%) at 70% V̇O2max, while improving feelings of energy and focus. These findings may be attributable to caffeine, betaalanine, and arginine found within the investigated product and many other pre-workouts that have been shown to delay the onset of fatigue and reduce feelings of exertion (4,11,15,28,30,39,41,42,48). Consistent with many pre-workouts on the market, however, the product of Walsh et al (47) contained proprietary blends with the majority of ingredients (including caffeine) listed at unknown quantities.…”
Section: Introductionmentioning
confidence: 70%
“…Arginine is a conditionally essential amino acid that is involved in protein synthesis, the detoxification of ammonia, and its conversion to glucose as well as being catabolized to produce energy; in addition to these physiological functions, arginine has shown to have ergogenic potential [4]. Argininebased supplement may be used on an acute basis for delaying the onset of neuromuscular fatigue (i.e., PWCFT) and improving the ventilatory threshold [5].…”
Section: Introductionmentioning
confidence: 99%